2014
DOI: 10.1021/nl500548a
|View full text |Cite
|
Sign up to set email alerts
|

Carbon-Coated Na3V2(PO4)3 Embedded in Porous Carbon Matrix: An Ultrafast Na-Storage Cathode with the Potential of Outperforming Li Cathodes

Abstract: Sodium ion batteries are one of the realistic promising alternatives to the lithium analogues. However, neither theoretical energy/power density nor the practical values reach the values of Li cathodes. Poorer performance is expected owing to larger size, larger mass, and lower cell voltage. Nonetheless, sodium ion batteries are considered to be practically relevant in view of the abundance of the element Na. The arguments in favor of Li and to the disadvantage of Na would be completely obsolete if the specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
371
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 467 publications
(391 citation statements)
references
References 40 publications
(58 reference statements)
10
371
1
2
Order By: Relevance
“…k) Facile soft chemistry‐based double carbon‐embedding approach for (C@NVP)@pC. Reproduced with permission 135. Copyright 2014, American Chemical Society.…”
Section: Strategies To Enhance the Electrochemical Performance Of Polmentioning
confidence: 99%
“…k) Facile soft chemistry‐based double carbon‐embedding approach for (C@NVP)@pC. Reproduced with permission 135. Copyright 2014, American Chemical Society.…”
Section: Strategies To Enhance the Electrochemical Performance Of Polmentioning
confidence: 99%
“…Recently, the use of hierarchical carbon to decorate the Na 3 V 2 (PO 4 ) 3 electrode has been widely adopted to make high‐performance Na 3 V 2 (PO 4 ) 3 electrodes 11, 12, 60, 105, 111, 112, 113, 114, 115, 116. Zhu et al reported a carbon‐coated Na 3 V 2 (PO 4 ) 3 embedded in porous carbon with remarkable rate capability of 44 mAh g –1 at a current rate of 200 C ( Figure 6 d) 114.…”
Section: Single‐phosphate Materials For Na Storagementioning
confidence: 99%
“…Zhu et al reported a carbon‐coated Na 3 V 2 (PO 4 ) 3 embedded in porous carbon with remarkable rate capability of 44 mAh g –1 at a current rate of 200 C ( Figure 6 d) 114. Xu et al have also synthesized a layer‐by‐layer Na 3 V 2 (PO 4 ) 3 @rGO material with ≈3% rGO and 0.5% amorphous carbon, which shows excellent rate capability (41 mAh g –1 at a current rate of 200 C) and cyclability (70.0% capacity retention after 15 000 cycles at 50 C) 112.…”
Section: Single‐phosphate Materials For Na Storagementioning
confidence: 99%
See 1 more Smart Citation
“…To promote the practical application of the SIB technology, it is urgent to explore new host materials for Na + ions. A number of transition metal oxides, poly‐anionic, and Prussian blue compounds have been identified as promising cathode materials for SIBs 3. Meanwhile, the choices for anodes seem limited:4 only a few materials such as disordered carbons, Ti‐based intercalation compounds, a few metal alloys, oxides, and sulfides have displayed satisfactory Na + ‐ion storage capacities, among which low crystalline hard carbons are the most attractive ones for commercial application of SIBs due to their low price.…”
mentioning
confidence: 99%